PENERAPAN KEBIJAKAN FASILITAS MITRA UTAMAKEPABEANAN: MAMPUKAH MENURUNKAN COST OF TAXATION? - Murwendah, Murwendah; Tsanymahdy, Muhammad Raihan (UI Scholars Hub, 2021)
The Main Partner of Customs, which was implemented in 2015, aims to reduce dwelling-time rates, decrease logistics costs, and appreciate companies with good tax compliance. On the other hand, dwelling-time figures have not shown a significant decline in numbers with all the facilities provided. This study examines the Main Partner of Customs policy regarding the cost of taxation perspective at Tanjung Priok Port. The discussion of this research focuses on the burden carried by both the policymaker and the company. This research was conducted through a quantitative approach with a post-positivist paradigm. The data collection techniques for this research are literature studies and field observation through in-depth interviews, where the research results are analyzed using qualitative data analysis techniques. This study indicates that the Main Partner of Customs policy becomes more efficient when considered from administrative cost. The division of authority and duties in the administrative process, simplification of policies and administration, and division of workload between the Directorate General of Customs and Excise and client coordinators at ports can reduce the administrative burden from the government side. In terms of compliance costs, the Main Partner of Customs policy is considered to reduce the burden on the company in terms of time and encourage the improvement of the company's quality in completing customs obligations. However, psychological challenges remain in the path of its implementation. According to the findings, there is a need for an alternative application for companies who wish to become the Main Customs Partner so that the process of selecting the Main Customs Partner is fair. In addition, the issue of legal certainty in this policy can be improved by adopting one-stop coordination with relevant Ministries/Agencies regarding prohibitions and restrictions on export-import activities.